Minimally invasive esophagectomy with three fields (2.5-field and cervical-field) lymph node dissection with esophageal suspension method - Zheng, Bin; Zhang, Shuliang; Zeng, Taidui; Zheng, Wei; Chen, Chun (Journal of Thoracic Disease, 2019)
Esophagectomy, including complete primary tumor removal and radical lymphadenectomy with or without cervical lymphadenectomy, has been accepted as a radical esophagectomy that remains a standard treatment choice for esophageal squamous cell carcinoma (ESCC) (1,2). Studies have reported low incidences of pneumonia and mortality, similar medium-term, stage-specific survival in minimally invasive esophagectomy (MIE), compared with those reports form open esophagectomy (1,3).